2022
DOI: 10.1007/s12035-022-02844-0
|View full text |Cite
|
Sign up to set email alerts
|

Hotair and Malat1 Long Noncoding RNAs Regulate Bdnf Expression and Oligodendrocyte Precursor Cell Differentiation

Abstract: BDNF has remarkable protective roles in the central nervous system to ensure neurons and glial cells survival and proper functions. The regulatory processes behind the BDNF expression have not been revealed completely. Here, it was explored whether Malat1 and Hotair lncRNAs play roles in the regulation of Bdnf expression level, modification of fingolimod downstream pathway, and oligodendrocytes precursor cells maturation. By Hotair and Malat1 downregulation, their regulatory mechanism on Bdnf expression was in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…A study has showed that oligodendrocytes in the spinal cord and optic nerve express BDNF mRNA and the expression is increased in Long-Evans shaker rats that lack CNS myelin due to the MBP gene mutation [47]. Another study found that fingolimod treatment resulted in increased BDNF mRNA concomitant with increased OPC differentiation in rat OPC culture [48]. Our results confirm the expression of BDNF in oligodendrocytes in certain brain regions.…”
Section: Discussionsupporting
confidence: 82%
“…A study has showed that oligodendrocytes in the spinal cord and optic nerve express BDNF mRNA and the expression is increased in Long-Evans shaker rats that lack CNS myelin due to the MBP gene mutation [47]. Another study found that fingolimod treatment resulted in increased BDNF mRNA concomitant with increased OPC differentiation in rat OPC culture [48]. Our results confirm the expression of BDNF in oligodendrocytes in certain brain regions.…”
Section: Discussionsupporting
confidence: 82%
“…The data on neurotrophins receptors expression are in line with emerging roles of these molecules in in OPC differentiation and maturation, which are still poorly described, as recently proved for BDNF ( Khani-Habibabadi et al, 2022 ). In the first part of this study, in fact, we demonstrated that mixed OPC/astrocyte cultures produce NGF and respond to NGF during OPC differentiation and OL maturation; that NGF receptors are dynamically expressed throughout the NSC lineage and OPC differentiation process, and that neutralization of endogenous NGF determines an impairment in OPC differentiation.…”
Section: Discussionmentioning
confidence: 57%
“…This is supported by evidences that HOTAIR -EZH2-miRNA-141 signaling drives expressional changes in BDNF, and regulates the differentiation of dopaminergic neuron-like cells from human amniotic epithelial stem cells (HuAESCs) (Liu et al 2018b ). Along similar lines, Khani‑Habibabadi et al have recently implicated HOTAIR in the regulation of oligodendrocyte precursor cell differentiation (Khani-Habibabadi et al 2022 ).…”
Section: Hotair In Non-oncological Brain Pathophysiological ...mentioning
confidence: 84%